Autologous Microfragmented Adipose Tissue Reduces the Catabolic and Fibrosis Response in an In Vitro Model of Tendon Cell Inflammation. (5th December 2019) - Viganò, Marco; Lugano, Gaia; Perucca Orfei, Carlotta; Menon, Alessandra; Ragni, Enrico; Colombini, Alessandra; De Luca, Paola; Randelli, Pietro; de Girolamo, Laura
Abstract : Background . Mesenchymal stem cells (MSCs) emerged as a promising therapy for tendon pathologies. Microfragmented adipose tissue ( μ FAT) represents a convenient autologous product for the application of MSC-based therapies in the clinical setting. In the present study, the ability of μ FAT to counteract inflammatory processes induced by IL-1 β on human tendon cells (TCs) was evaluated. Methods . Cell viability and proliferation were evaluated after 48 hours of transwell coculture of TCs and autologous μ FAT in the presence or absence of IL-1 β . Gene expression of scleraxis, collagen type I and type III, metalloproteinases-1 and -3, and cyclooxygenase-2 was evaluated by real-time RT-PCR. The content of VEGF, IL-1Ra, TNF α, and IL-6 was evaluated by ELISA. Results . IL-1 β -treated TCs showed augmented collagen type III, metalloproteases, and cyclooxygenase-2 expression. μ FAT was able to reduce the expression of collagen type III and metalloproteases-1 in a significant manner, and at the same time, it enhanced the production of VEGF, IL-1Ra, and IL-6. Conclusions . In this in vitro model of tendon cell inflammation, the paracrine action of μ FAT, exerted by anti-inflammatory molecules and growth factors, was able to inhibit the expression of fibrosis and catabolic markers. Then, these results suggest that the application of μ FAT may represent an effective conservative or adjuvant therapy for the treatment of tendon disorders.